ANALISIS TINGKAT PENERIMAAN PENGGUNAAN NOTION DALAM MENERAPKAN AGILE SCRUM PADA PROYEK GAMELAN METAVERSE - Yohanes Malvin Buntoro; Putri Nastiti; Clara Hetty Primasari; Yohanes Priadi Wibisono; Julius Galih Prima Negara (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
The Gamelan Metaverse Project is a project for creating the Virtual Reality Metaverse Gamelan application with an Agile Scrum framework that aims to educate people about gamelan and how to play it. This project was carried out by apprentices from PT Arutala, which consisted of students from several universities in Yogyakarta. Project participants were asked to use a project management tool, Notion, in the hope of facilitating coordination and reducing miscommunication. The purpose of this study is to determine what factors influence apprentices' acceptance of Notion at PT Arutala, as well as how helpful the apprentices are when using Notion. This research will use the Technology Acceptance Model (TAM) model in analyzing Notion acceptance factors for PT Arutala apprentices. The author used the TAM model to investigate the variables that influenced the acceptance of Notion among the Arutala internship.The research used seven hypotheses in the TAM model to determine its level of acceptance, and found that all hypotheses had a positive relationship, with six of them are significant and one is not significant.These results was obtained by running path coefficient and t-stistic test on the TAM model that author used.This research concludes that while the interns have acknowledged the benefits form using Notion, it requires time for them to incorporate its usage into their project management routine.